2016
DOI: 10.18632/oncotarget.10301
|View full text |Cite
|
Sign up to set email alerts
|

miR-200b is a key regulator of tumor progression and metabolism targeting lactate dehydrogenase A in human malignant glioma

Abstract: Lactate dehydrogenase A (LDHA) is involved in various cancers. In this study, we investigated the expression and function of LDHA in glioma. We found that LDHA was up-regulated in glioma samples. Furthermore, we found that overexpression of LDHA promoted proliferation, invasion and glycolysis in glioma cells. Luciferase reporter assays confirmed that LDHA was a direct target of miR-200b. miR-200b was found to be down-regulated in glioma samples, which was inversely correlated with LDHA expression. Repression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…In the present study, we have demonstrated that miR‐200b‐3p and miR‐200c‐3p have significantly reduced expression in GBM tissues and that their downregulation is negatively correlated with HMGB3 overexpression. Dysregulation of miR‐200 family members occurs in a variety of cancers, including in GBM where miR‐200b was shown to negatively regulate tumour progression and metabolism by targeting lactate dehydrogenase A . That the miR‐200 family members tend to play a tumour‐suppressive role further substantiates our study's findings, which strongly suggest a tumour‐suppressive role for miR‐200b‐3p and miR‐200c‐3p through HMGB3 inhibition.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, we have demonstrated that miR‐200b‐3p and miR‐200c‐3p have significantly reduced expression in GBM tissues and that their downregulation is negatively correlated with HMGB3 overexpression. Dysregulation of miR‐200 family members occurs in a variety of cancers, including in GBM where miR‐200b was shown to negatively regulate tumour progression and metabolism by targeting lactate dehydrogenase A . That the miR‐200 family members tend to play a tumour‐suppressive role further substantiates our study's findings, which strongly suggest a tumour‐suppressive role for miR‐200b‐3p and miR‐200c‐3p through HMGB3 inhibition.…”
Section: Discussionsupporting
confidence: 84%
“…Our research showed that miR-200b and miR-200c expression levels were decreased in breast cancer cells after exposure of hypoxia, uncovering that they might be associated with regulation of hypoxia. Previous studies demonstrated that miR-200b and miR-200c could inhibit glycolysis in cancers by targeting lactate dehydrogenase A and sirtuin 2 [30,31]. Additionally, miR-200b and miR-200c could suppress migration and invasion of breast cancer cells by regulating ezrin-radixin-moesin and fucosyltransferase-4 [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…MiR200b reduces iNOS expression and NO production and limits the migratory potential of reactive microglia. Suppression of the glycolytic enzyme lactate dehydrogenase A (LDHA) and aerobic glycolysis likely underlies the miRNA action (S. Hu et al, ); (Table ).…”
Section: Micrornas Promoting Pro‐regenerative Microglia Phenotype Andmentioning
confidence: 99%